Conditioning of sleeping disorders in women using and not using hormonal replacement therapy - Wilczak, Maciej; Samulak, Dariusz; Mojs, Ewa; Michalska, Magdalena Monika; Kaczmarek, Łukasz (Menopause Review/Przegląd Menopauzalny, 2010)
Symptoms accompanying the changes occurring in a female organism in the climacteric period constitute more frequently a major health-related problem and via its influence on the quality of life, they also become social-related problems concerning many millions of women worldwide. The aim of the study was to estimate the conditioning of sleeping disorders in women using and not using hormonal replacement therapy (HRT). 90 patients between 15 and 80 years of age participated in the study (M = 49.81; SD = 11.69). Psychological tests and sleeping disorders tests that were used: Courtauld Emotional Control, Beck Depression Inventory, Satisfaction With Life Scale, State-Trait Anxiety Inventory STAI, Stanford Sleepiness Scale, Epworth Sleepiness Scale, Athens Insomnia Scale. The analysis of the results included first of all measuring of r-Pearson’s correlation between sleeping disorders such as difficulties in falling asleep, maintaining sleep or awakening too early and groups of variables such as the level of psychic life (satisfaction with life as a positive indicator and depression as an indicator of disorders), control of emotions (anger, depression and anxiety as well as general control indicator) and self-esteem (general self-esteem, competences, being loved, popularity, leadership features, self-control, moral self-acceptance, physical attractiveness, vitality, integration of identity, defensive self-enhancement).